2018
DOI: 10.1097/dss.0000000000001429
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of the Face and Mohs Micrographic Surgery: Nationwide Mortality Data Analysis

Abstract: Patients with melanoma of the face treated with MMS had similar melanoma-specific mortality or overall survival outcome as patients treated by other surgical modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 30 publications
4
38
1
Order By: Relevance
“…Notably, our study analysed selected patients with lower‐extremity MMs, which were mostly ALMs with poor prognoses and necessitated inguinal SLNBs. Moreover, our data indirectly allude to more favourable results obtained via MMS than in previous studies …”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Notably, our study analysed selected patients with lower‐extremity MMs, which were mostly ALMs with poor prognoses and necessitated inguinal SLNBs. Moreover, our data indirectly allude to more favourable results obtained via MMS than in previous studies …”
Section: Discussionsupporting
confidence: 80%
“…reviewed the outcomes of 625 patients with melanoma and found that MMS had several advantages over conventional surgery, including low local recurrence rates and smaller wounds. In our study, the local recurrence rate after MMS was 7%, which is also very low compared with previously reported rates and highlights the effectiveness of MMS for successfully managing acral melanoma.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations